Secure Multicast Routing Protocol in Manets Using Efficient ECGDH Algorithm - Gopi Arepalli; Suresh Babu Erukula (International Journal of Electrical and Computer Engineering (IJECE), 2016)
An Ad-hoc Network covers a set of autonomous mobile nodes that communicates through wireless communication in an infrastructure-less environment. Mostly MANETs are used in group communication mechanisms like military applications, emergency search, rescue operations, vehicular ad-hoc communications and mining operations etc. In such type of networks, group communication is takes place by multicasting technique. Communication and collaboration is necessary among the nodes in the groups in multicast protocols. PUMA has the best multicast routing protocol compared to tree and mesh based multicast protocols although it suffers from security issues. PUMA mainly suffers from Man In The middle attack. MITM attack generates traffic flow, drop the packets and miscommunicate the neighbor nodes with false hop count. So defending from MITM attack we designed a new mechanism called Elliptic Curve Group Diffie-Hellman (ECGDH). This paper compares results of PUMA [1] routing protocol with legitimate, under attack and after providing security against attack. Finally we observed ECGDH [2] gives efficient results even attack has happened.